Cell technologies in retinitis pigmentosa treatment - Zeinet Akhmedyanova; Manshuk Yeltokova; Zhanna Bayanbayeva; Assel Khassenova (Ķazaķstannyṇ Klinikalyķ Medicinasy, 2022)
The growing crucial problem in practical ophthalmology relates to growth of hereditary degenerative diseases of the retina, in particular retinitis, causing progressive loss of visual functions. According to international estimates, the incidence rate of hereditary dystrophy contains 1 case per 3000 population. With the development of biomedical cell technologies, transplantation of stem (autologous and allogeneic) cells is at the stage of active research. The article reviewed literature sources on prevalence, risk factors, etiopathogenesis, diagnosis, clinical picture and treatment of retinitis pigmentosa.